Autoimmune Inner Ear Disease: Literature Review: Doença Autoimune do Ouvido Interno: Revisão da Literatura - Branco, Margarida; Caroça, Cristina; Campelo, Paula; Tinoco, Catarina; Caçador, Maria; Paço, João (Gazeta Médica, 2018)
Autoimmune hearing loss is a rare clinical entity usually representing a challenge diagnosis, corresponding often to the initial manifestation of a systemic autoimmune disease. It is characterized by the presence of sensorineural hearing loss, bilateral or asymmetrical, usually of progressive installation for weeks to months. In 50% of the cases associated with hearing loss, there is vestibular symptoms, tinnitus or ear fullness. Given the absence of specific tests that allow the definitive diagnosis, this is based on clinical suspicion and response to treatment with immunosuppressive therapy. The differential diagnosis is made through a detailed medical history with complete objective examination, as well as audiometric, laboratory and imaging tests to exclude other sensorineural hearing loss etiologies. The rarity of the disease, wide spectrum of clinical manifestations, absence of randomized studies that demonstrate the efficacy of the treatment and absence of long-term results of this disease are a challenge. With this article the authors intend to carry out a review of the topic in order to facilitate the early identification of this condition and allow proper institution of treatment.